Effect of soil conditioner (UGmax) application on the content of phenols and glycoalkaloids in potato tubers - Marek GUGAŁA; Krystyna ZARZECKA; Anna SIKORSKA; Krzysztof KAPELA; Marek NIEWĘGŁOWSKI; Ewa KRASNODĘBSKA (Plant, Soil and Environment, 2017)
The objective of the study was to determine the effect of the soil conditioner UGmax application on phenol and glycoalkaloid content in the tubers of two table potato cultivars. The following factors were examined: factor I - cultivars: Satina and Tajfun; factor II - five application methods of the soil conditioner UGmax: (1) control - no UGmax application; (2) 1.0 L/ha UGmax before planting; (3) 0.5 L/ha UGmax before planting + 0.25 L/ha at potato height of 10-15 cm + 0.25 L/ha in flower bud phase; (4) 1.0 L/ha UGmax before planting + 0.50 L/ha at potato height of 10-15 cm + in 0.50 L/ha in flower bud phase; (5) UGmax applied after emergence when plants were 10-15 cm high at the rate of 0.5 L/ha, and at the stage of flower buds at the rate of 0.5 L/ha. The highest concentration of phenols and glycoalkaloids was recorded in plots where UGmax was applied prior to potato planting at the rate of 1.0 L/ha, when plants were 10-15 cm high at the rate of 0.5 L/ha and at the stage of flower buds at the rate of 0.5 L/ha.